First-Principles Investigation on Structural and Electronic Properties of Ferromagnetic Fe2P4O12 - Rerksompus, Pathompong; Sarasamak, Kanoknan; Boonchom, Banjong; Thanomngam, Pitiporn (My University, 2015)
Structural and electronic properties of Fe2P4O12 have been investigated using first-principles calculation technique. The results indicated that the Fe2P4O12 structure is monoclinic of C2/c with lattice parameters of a = 12.228 Å, b = 8.530 Å, c = 9.835 Å and β = 118.67°. Two nonequivalent octahedral FeO6 from the calculation have an average Fe-O distance of 2.143 Å. Both FeO6 are dominated by covalent interactions assigned to Fe3d and O2p at the valent electronic states. The DOS calculation gives well explanation on its half-metallic ferromagnetic property. These results are in very good agreement with the previous experimental reports. © 2015
Keywords: Electronic property; Ferromagnetic materials; First-principles calculation; Structure